Caregiving Intensity and Mortality in Older Women, Accounting for Time-Varying and Lagged Caregiver Status: The Caregiver-Study of Osteoporotic Fractures Study. (12th January 2019) - Fredman, Lisa; Ranker, Lynsie R; Strunin, Lee; Smith, Meghan L; Applebaum, Katie M
Abstract: Background and Objectives: Caregiving is associated with reduced mortality in recent studies. Investigations of caregiving intensity may reveal an underlying mechanism. However, studies of caregiving intensity and mortality have mixed results, perhaps due to imprecise measurement of caregiving intensity, not accounting for healthier persons likely having greater caregiving involvement, or temporal changes in intensity. We examined the relationship between caregiving intensity (based on tasks performed) and mortality, treating intensity and health status as time-varying, and lagging exposure. Research Design and Methods: Caregiving tasks among 1, 069 women in the Caregiver-Study of Osteoporotic Fractures study (35% caregivers) were assessed at 5 interviews conducted between 1999 and 2009. Caregivers were categorized as high intensity if they assisted a person with dressing, transferring, bathing, or toileting; or as low intensity if they assisted with other instrumental or basic activities of daily living (I/ADLs). Alternatively, high intensity was defined as assisting with more than the median number of I/ADL tasks (median-based measure). Mortality was assessed through 2011. Cox proportional hazards models estimated adjusted hazard ratios (aHR) and 95% confidence intervals based on concurrent intensity, and lagging exposure 2 years. Results: High-intensity caregivers had significantly lower mortality using the median-based measure after lagging exposure (aHR = 0.55, 0.34–0.89). Similar, but not statistically significant associations were observed in non-lagged analyses (aHR = 0.54, 0.29–1.04) and task-specific intensity (aHRs were 0.61 and 0.51). Low-intensity caregivers had similar mortality rates to noncaregivers in all analyses. Discussion and Implications: Among older women, high-intensity caregivers had lower mortality rates than noncaregivers. Whether this association extends to other populations merits investigation.